2016
DOI: 10.1186/s40621-016-0092-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of Ugandan District Hospital orthopedic units in the care of vulnerable road users: a cross-sectional study

Abstract: BackgroundMusculoskeletal injuries are a common cause of morbidity after road traffic injury (RTI) in motorizing countries. District hospitals provide front-line orthopedic care in Uganda and other sub-Saharan African nations. Improving care at the district hospital level is an important component of the World Health Organization’s strategy for surgical and trauma systems strengthening, but the data necessary to inform RTI safety and care initiatives has previously been insufficient at the district hospital le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The results from this study are comparable to several recent extremity fracture studies conducted in metropolitan and rural Ugandan communities with respect to patient demographics and treatment costs. [ 3 , 4 , 6 , 7 , 15 ] Therefore, we believe the sample to be representative of this population. [ 3 , 4 , 6 , 7 , 15 ] A recent study at a large publicly funded region hospital in Southwestern Uganda assessed the effect of surgical costs, for all types of surgical treatment, on impoverishment.…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study are comparable to several recent extremity fracture studies conducted in metropolitan and rural Ugandan communities with respect to patient demographics and treatment costs. [ 3 , 4 , 6 , 7 , 15 ] Therefore, we believe the sample to be representative of this population. [ 3 , 4 , 6 , 7 , 15 ] A recent study at a large publicly funded region hospital in Southwestern Uganda assessed the effect of surgical costs, for all types of surgical treatment, on impoverishment.…”
Section: Discussionmentioning
confidence: 99%
“…Males are almost three times more affected by orthopedic fractures compared to females [7]. Different studies found out frequently more affected by road traffic crashes than females [8][9][10][11][12][13][14]. The younger age groups are most commonly affected in orthopedic crash fractures [1,10,11,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…If so, this situation is likely to change quickly as high-speed modern roads are being built very rapidly, associated with post-war development and new investments. 18,19 Regional variations in the etiology of MLL have previously been reported in other African countries like Nigeria. These studies found that whereas diabetic complications were the main causes for amputation in some areas of the country, in others trauma was the most common cause.…”
Section: Discussionmentioning
confidence: 85%